Household knights, chamber knights and king's knights: the development of the royal knight in fourteenth-century England. Issue 1 (1st January 2019) - Hefferan, Matthew
ABSTRACT: The fourteenth century witnessed a considerable change in the way in which knights were retained in royal service in England. The system of retaining 'household knights', which had been in operation since at least the twelfth century, gave way to a new system based around the retaining of 'chamber knights' and 'king's knights'. These new ranks were retained in different ways to the household knights and often performed different functions. Consequently, the place they occupied in fourteenth-century kingship was markedly different. Despite the significance of this development, the scholarship on it has been limited and often contradictory. This article offers a detailed reassessment of how and why this development occurred and what its impacts were for the fourteenth-century polity.